Interleukin-6 and C-reactive protein, successful aging, and mortality: the PolSenior study - Puzianowska-Kuźnicka, Monika; Owczarz, Magdalena; Wieczorowska-Tobis, Katarzyna; Nadrowski, Pawel; Chudek, Jerzy; Slusarczyk, Przemyslaw; Skalska, Anna; Jonas, Marta; Franek, Edward; Mossakowska, Malgorzata (Immunity & ageing, 2016)
Background In the elderly, chronic low-grade inflammation (inflammaging) is a risk factor for the development of aging-related diseases and frailty. Using data from several thousand Eastern Europeans aged 65 years and older, we investigated whether the serum levels of two proinflammatory factors, interleukin-6 (IL-6) and C-reactive protein (CRP), were associated with physical and cognitive performance, and could predict mortality in successfully aging elderly. Results IL-6 and CRP levels systematically increased in an age-dependent manner in the entire study group (IL-6: n = 3496 individuals, p < 0.001 and CRP: n = 3632, p = 0.003), and in the subgroup of successfully aging individuals who had never been diagnosed with cardiovascular disease, myocardial infarction, stroke, type 2 diabetes, or cancer, and had a Mini Mental State Examination (MMSE) score ≥24 and a Katz Activities of Daily Living (ADL) score ≥5 (IL-6: n = 1258, p < 0.001 and CRP: n = 1312, p < 0.001). In the subgroup of individuals suffering from aging-related diseases/disability, only IL-6 increased with age (IL-6: n = 2238, p < 0.001 and CRP: n = 2320, p = 0.249). IL-6 and CRP levels were lower in successfully aging individuals than in the remaining study participants (both p < 0.001). Higher IL-6 and CRP levels were associated with poorer physical performance (lower ADL score) and poorer cognitive performance (lower MMSE score) (both p < 0.001). This association remained significant after adjusting for age, gender, BMI, lipids, estimated glomerular filtration rate, and smoking status. Longer survival was associated with lower concentrations of IL-6 and CRP not only in individuals with aging-related diseases/disability (HR = 1.063 per each pg/mL, 95 % CI: 1.052-1.074, p < 0.001 and HR = 1.020 per each mg/L, 95 % CI: 1.015-1.025, p < 0.001, respectively) but also in the successfully aging subgroup (HR = 1.163 per each pg/mL, 95 % CI: 1.128-1.199, p < 0.001 and HR = 1.074 per each mg/L, 95 % CI: 1.047-1.100, p < 0.001, respectively). These associations remained significant after adjusting for age, gender, BMI, lipids and smoking status. The Kaplan-Meier survival curves showed similar results (all p < 0.001). Conclusions Both IL-6 and CRP levels were good predictors of physical and cognitive performance and the risk of mortality in both the entire elderly population and in successfully aging individuals.